The appeal for adhesion in the Peruvian Civil Procedure Code: An approach to the subject - Cruz Lezcano, Carlos (2008)
The Civil Procedural Code gathers the figure of the preference to the appeal resource, as it is in the Code of Civil Procedures of 1912; in both cases, without a notorious development. In this perspective, the author approaches the subject under the own theoretical point of view of the appeal resource, developing each one of the principles and institutions that are essential; getting to base, in front of the position that it identifies like ample, a position to which characterizes as restricted, and according to which the preference  to  the appeal is an exceptional resource of relative autonomy and restricted  reach, very similar to the incidental appeal of the Italian civil process, therefore very different from the opposition to the appeal of  the procedural  right in Spain.